A brief review of the role of training in near-tool effects - Brown, Liana E.; Goodale, Melvyn A. (Frontiers in Psychology, 2013)
Research suggests that, like near-hand effects, visual targets appearing near the tip of a hand-held real or virtual tool are treated differently than other targets. This paper reviews neurological and behavioural evidence relevant to near-tool effects and describes how the effect varies with the functional properties of the tool and the knowledge of the participant. In particular, the paper proposes that motor learning and control plays a key role in the appearance of near-tool effects.